GE_GERICHTE P/15030/2011 vom 20. Dezember 2012 - GE Cour de justice (2012)
TENTATIVE(DROIT PÉNAL); MEURTRE; CONTRAINTE SEXUELLE; FIXATION DE LA PEINE; INDEMNITÉ(EN GÉNÉRAL); PLAIGNANT ; AVOCAT; HONORAIRES | CP.111; CP.189.3; CP.47